The Influence of Organizational Culture, Organizational Commitment, Competency and Work Environment on Employee Performance - Manik Adi Prakoso; Istiatin Istiatin; Sudarwati Sudarwati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of organizational culture, organizational commitment, competence, and work environment on employee performance at the Center for Teachers and Education Personnel of Central Java Province. The research method used is quantitative research with a descriptive approach. The population in this study were all 130 employees of BBGTK of Central Java Province, with a sampling technique using the census method so that the entire population was used as a research sample. The data collection technique was carried out through distributing questionnaires. Data analysis used multiple linear regression with the help of the SPSS 27 program. The results of the study indicate that organizational culture, organizational commitment, competence, and work environment partially and simultaneously have a significant effect on employee performance. The results of the determination coefficient test show an Adjusted R Square value of 0.857, which means that the variables of organizational culture, organizational commitment, competence, and work environment are able to explain the influence on employee performance by 85.7%, while the remaining 14.3% is influenced by other variables outside the study. Thus, improving employee performance at BBGTK of Central Java Province can be done through strengthening organizational culture, increasing organizational commitment, developing competence, and creating a comfortable and conducive work environment. Keywords: Organizational Culture, Organizational Commitment, Competence, Work Environment, Employee Performance.